An assessment of the extent to which the city of Johannesburg's Rea Vaya bus rapid transit system is achieving its intended socio-economic and political objectives - Mjiyako, Dominic Ntokozo (Graduate School of Development Policy and Practice, 2022)
South Africa is ranked number one in the world as the most unequal society by the World Bank. Inequalities are largely manifested in income, education and spatial arrangements, as well as access to opportunities and public services. My dissertation examines the impact of the City of Johannesburg's Rea Vaya Bus Rapid Transit (BRT) system, and the transit-oriented development programme, known as Corridors of Freedom, in transforming the mini-bus taxi industry; providing safe and reliable public transport to previously marginalised communities; and to mitigate the legacy of apartheid spatial planning. The research examines the policy objectives of the Rea Vaya BRT system as part of the larger Corridors of Freedom capital programme, which aims to create development nodes to densify the City and improve mobility, and in turn enhance social integration. The research outlines the implementation of Rea Vaya over the past ten years, and explores the impact of the service on the City's commuters and the mini-bus taxi operators. A key argument of the paper is that while anecdotal evidence exists that the Rea Vaya BRT functions optimally, an evaluation study of the City's continued public investment is critical to ascertain whether the project is achieving its intended socio-political and economic objectives.